2008
DOI: 10.4049/jimmunol.181.3.1798
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Adaptive Regulatory CD4 Cells That Can Reverse Type I Diabetes Become Oligoclonal Long-Term Protective Memory Cells

Abstract: Type 1 diabetes is a CD4 cell-dependent disease that results from destruction of insulin-producing β cells in pancreatic islets. An ideal therapy would reverse diabetes shortly after onset when islet function in not yet fully ablated, and also prevent re-emergence of disease through the generation of memory cells that control the autoimmune response. In this study, we show that adaptive/induced polyclonal regulatory (TR) cells, which contain islet-reactive cells, fulfill these criteria in the NOD mouse model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 43 publications
5
48
0
Order By: Relevance
“…Studies have shown that both thymic-derived nTregs and in vitroexpanded iTregs can be used to prevent disease in mouse models of human disease when given prior to or very shortly after disease induction (14)(15)(16)18). The use of Ag-specific as opposed to polyclonal Tregs is more attractive as a cellular therapy because of the potential to target immunosuppression to the affected organ while leaving the rest of the immune system capable of mounting normal responses against infection or cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that both thymic-derived nTregs and in vitroexpanded iTregs can be used to prevent disease in mouse models of human disease when given prior to or very shortly after disease induction (14)(15)(16)18). The use of Ag-specific as opposed to polyclonal Tregs is more attractive as a cellular therapy because of the potential to target immunosuppression to the affected organ while leaving the rest of the immune system capable of mounting normal responses against infection or cancer.…”
Section: Discussionmentioning
confidence: 99%
“…iTregs share functional capabilities with nTregs in that they are suppressive both in vitro and in vivo (9)(10)(11)(12)(13). For example, the transfer of iTregs reduced the severity of experimental autoimmune encephalmyelitis, prevented the development of diabetes and autoimmune gastritis (AIG), and alleviated the severity of viral-induced ocular inflammatory disease (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: B Oth Thymus-derived Natural Regulatory T Cells (Ntregs) Andmentioning
confidence: 99%
“…One possibility is that persistence of a peptide on the class II molecule provides an advantage for stable CD4 memory generation and maintenance. Although it is known that antigen persistence is not required to generate memory cells (42)(43)(44)(45), it is possible that continued opportunities to engage the CD4 T cells agonist ligand provides some advantage in the quantity or quality of memory T cells (29,(46)(47)(48)(49). Also, engagement of CD4 T cells, particularly follicular helper T cells, with antigen-specific B cells in the germinal center may be most efficient and long-lived for stable peptide:class II complexes (23).…”
Section: Discussionmentioning
confidence: 99%
“…The idea is to compensate a presumed deficiency in tolerogenic cells or tolerogenic cell/molecular signaling pathways by transferring cell types with immunomodulatory capacity. Specifically, both ex vivo expanded Tregs or induced CD4 + CD25 + Foxp3 + Tregs (iTreg) have been shown to control ongoing autoimmunity and either prevent progression to diabetes or protect syngeneic islet grafts and/or allow -cell recovery, thus inducing diabetes remission in NOD mice (Tang & Bluestone, 2006;Weber et al, 2006;Luo et al, 2007;Godebu et al, 2008). It is unclear whether antigen specificity is critically important in this approach because both nonspecifically-expanded polyclonal or induced Tregs and islet antigen-specific Tregs have shown efficacy in controlling the disease.…”
Section: Cell Therapy In Type 1 Diabetesmentioning
confidence: 99%